Implementasi Keamanan Jaringan Komputer Menggunakan Standard Access Control List pada Jaringan LAN dan WLAN - Raden Deasy Mandasari; Adam Maulidi Kurnia (Website, 2023)
Computer network security has become crucial in managing and protecting sensitive data transmitted through networks. Effective implementation of security measures on every device connected to the network is a critical aspect. This article discusses the use of Standard Access Control List (ACL) as a solution to enhance computer network security, both in Local Area Networks (LANs) and Wireless Local Area Networks (WLANs). This method serves as an access rights provider in computer networks by denying access from unrecognized devices to prevent security vulnerabilities. The results of simulations indicate that using Standard Access Control List successfully blocks computer lab client access to the server, thereby reducing the potential for cyber attacks and improving computer network security.